The Effect of Financial Literacy, Lifestyle, and Self-Control on the Consumer Behavior of Students Using Buy Now Pay Later (BNPL) with Financial Attitude as a Mediation Variable - Siti Syahmira; Nur Anita (Universitas KH. Abdul Chalim Mojokerto, 2025)
Using financial attitude as a mediating variable, this study attempts to examine the impact of lifestyle, self-control, and financial literacy on the purchasing behavior of students who utilize Buy Now Pay Later (BNPL) services. This study's backdrop is students' growing usage of BNPL services like Shopee Paylater, which has resulted in a propensity for consumptive behavior because of insufficient financial literacy, consumptive lifestyles, and a lack of self-control. The study employs a survey method and a quantitative approach, distributing questionnaires to current accounting students at multiple Bengkalis institutions. The WarpPLS 7.0 program was used to analyze the data using structural equation modeling (SEM) based on partial least squares (PLS). The findings demonstrated that whereas lifestyle and self-control had a favorable and substantial impact on consumptive behavior, financial literacy had a positive but negligible influence. Furthermore, while self-control has little bearing on financial views, lifestyle and financial knowledge do. Although it has been demonstrated that financial attitudes significantly and favorably influence consumptive behavior, they do not function as a mediation factor in the link between independent and dependent variables. In conclusion, lifestyle and self-control have a greater impact on students' consumptive behavior than financial literacy.